Characteristics of coffee producers and plantations in the northern region of the state of Chiapas - Vázquez-López, Patricia; Espinoza-Arellano, José de Jesús; González-Mancilla, Apolinar; Guerrero-Ramos, Liliana Angélica (Revista Mexicana de Ciencias Agrícolas, 2022)
Coffee is one of the most consumed agricultural products in the world. Mexico has a planted area of 710 431 ha and a production volume of 953 682 t. Despite its importance, in Mexico there is a lack of regional studies on the characteristics of coffee producers and plantations that serve as a basis for public policy decision-making. The objective of this work was to identify the characteristics of coffee producers and plantations in the municipality of Pantepec, Chiapas. A questionnaire of 76 questions was applied, which was divided into six blocks: informant data, plantation data, labor, financing and commercialization. The sample consisted of 61 producers from five localities of the municipality of Pantepec, Chiapas. The results indicate that producers are on average 41 years old and have low schooling. They have an area of less than two hectares, so the producers have to supplement their income with other activities. Eighty percent produce the landrace variety with renewed plantations, finding that 34.4% replanted two years earlier and 97% used between 100 and 600 new plants. Ninety-five percent of producers obtain yields between 0 and 600 kg ha-1. Coffee cultivation is an activity that generates roots in the population, however, it requires options that give it added value to generate employment and income in the region of study.
Keywords: Coffea arabica L.; added value; family roots; Pantepec